2013
DOI: 10.1080/00405000.2013.813664
|View full text |Cite
|
Sign up to set email alerts
|

Surface roughness properties of polyester woven fabrics after abrasion

Abstract: Effect of abrasion on surface roughness properties of textured polyester woven fabrics has been investigated. The effects of weft density, weft yarn filament number, fiber fineness, and weave pattern on surface roughness after abrasion were studied. Surface roughness values of control fabric (not abraded) and abraded fabrics after four different abrasion cycles were discussed according to different constructional parameters. Surface roughness values of fabrics changed according to abrasion cycles and the chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 19 publications
(18 reference statements)
1
5
0
1
Order By: Relevance
“…Yarn breakages were observed at 40.000 rubbing cycles for rPET-36R having the lowest number of filaments (36F) while it was 12.000-15.000 for rPET-72R having the highest number of filaments (72F). As similar to this result, Akgun (2014) reported that high number of filaments in yarn structure led to higher structural abrasion of the textured polyester woven fabric surfaces [22]. This case was explained that yarns with high number of filaments were more affected by abrasion and number of the pulled filaments from yarn surfaces increased as abrasion cycles increased.…”
Section: Abrasion Resistancesupporting
confidence: 65%
“…Yarn breakages were observed at 40.000 rubbing cycles for rPET-36R having the lowest number of filaments (36F) while it was 12.000-15.000 for rPET-72R having the highest number of filaments (72F). As similar to this result, Akgun (2014) reported that high number of filaments in yarn structure led to higher structural abrasion of the textured polyester woven fabric surfaces [22]. This case was explained that yarns with high number of filaments were more affected by abrasion and number of the pulled filaments from yarn surfaces increased as abrasion cycles increased.…”
Section: Abrasion Resistancesupporting
confidence: 65%
“…After 10,000 cycles the thickness of the fabric reached a stable value (0.576 mm), which represents a reduction of thickness of about 22%. In addition, a decrease of the fabric surface roughness has been observed as in the studies by Akgun 18 and Castellar et al 19 However, this paper focuses on compression and surface properties but some studies have also shown a link between shear or bending properties and friction sounds. 8 In addition, there are some experimental devices 8 that also allow fabric-to-fabric frictions.…”
Section: Analysis From 5000 To 20000 Cyclesmentioning
confidence: 85%
“…Studies related with polyester woven fabrics showed that fabrics with smooth surface properties could be produced using higher yarn density, by finer filament yarns, by decreased yarn float lengths, by increased fabric cover, and by improved fabric balance (Akgun, 2013;Akgun, 2014a;Akgun, in press;Akgun, Becerir & Alpay, 2012). The effects of some yarn properties and fabric constructional properties on surface roughness values of cotton woven fabrics revealed that roughness values of fabrics decreased as yarn fineness and yarn twist levels increased but as yarn ply number decreased.…”
Section: Introductionmentioning
confidence: 95%